Nanog expression in patients with squamous cell carcinoma of oropharynx in relation to immunohistochemical score - Kołodziej-Rzepa, Marta; Biesaga, Beata; Słonina, Dorota; Mucha-Małecka, Anna (Polish Journal of Pathology, 2022)
This study aimed to compare prognostic potential of Nanog expression analysed by three immunohistochemical scores in the group of 63 squamous cell carcinomas of oropharynx. Immunoreactivity of Nanog expression was analyzed by semiquantitative score, immunoreactive score and H-score. For all three scores, the cut-off points for Nanog overexpression and its lack, allowing for optimal separation of overall and disease free survival curves, were search by minimal p-value method. In semiquantitative score, the best separation of overall and disease free survival curves was obtain by cut-off point lack of staining vs. week/moderate/strong staining, although statistical significance was not reach (OS: HR = 1.016, p = 0.081, DFS: HR = 6.876, p = 0.061). The cut-off points for immunoreactive score and H-score were, respectively: 1 (OS: HR = 6.977, p = 0.014, DFS: HR = 6.002, p = 0.019) and 50 (OS: HR = 6.977, p = 0.014, DFS: HR = 6.002, p = 0.019). The cut-off points found for these two scores allow to identify the same subgroups of patients with lack of Nanog expression (11.1%) and its overexpression (88.9%). All patients with tumors characterized by lack of Nanog overexpression identifying by immunoreactive score and H-score survived 5 years without evidence of cancer progression. In multivariate analysis Nanog immunoreactivity analysed by QRS and IRS was independent prognostic factor for OS (HR = 10.195, p = 0.024). Immunohistochemical score using to distinguish Nanog overexpression or its lack has influence on prognostic potential of this biomarker.